In vitro and in vivo characteristics of doxorubicin-loaded cyclodextrine-based polyester modified gadolinium oxide nanoparticles: a versatile targeted theranostic system for tumour chemotherapy and molecular resonance imaging. (27th May 2020) - Mortezazadeh, Tohid; Gholibegloo, Elham; Khoobi, Mehdi; Alam, Nader Riyahi; Haghgoo, Soheila; Mesbahi, Asghar
Abstract: β -Cyclodextrine-based polyester was coated on the surface of gadolinium oxide nanoparticles (NPs) and then functionalised with folic acid to produce an efficient pH-sensitive targeted theranostic system (Gd2 O3 @PCD-FA) for doxorubicin delivery and magnetic resonance imaging (MRI). Gd2 O3 @PCD-FA was fully characterised by FTIR, vibrating sample magnetometer, TGA, XRD, SEM and TEM analyses. The dissolution profile of DOX showed a pH sensitive release. No significant toxicity was observed for the targeted NPs (Gd2 O3 @PCD-FA) and DOX-loaded NPs inhibiting M109 cells viability more efficiently than free DOX. Moreover, the negligible hemolytic activity of the targeted NPs showed their appropriate hemocompatibility. The preferential uptake was observed for the developed Gd2 O3 @PCD-FA-DOX NPs in comparison with Dotarem using T 1 - and T 2 -weighted MRI in the presence of folate receptor-positive and folate receptor-negative cancer cells (M109 and 4T1, respectively). Furthermore, in vivo studies revealed that Gd2 O3 @PCD-FA-DOX not only exhibited considerably relaxivity performance as a contrast agent for MRI, but also improved in vivo anti-tumour efficacy of the system. The results suggest that Gd2 O3 @PCD-FA-DOX improves its therapeutic efficacy in the treatment of solid tumours and also reduces the adverse effects, so it could be proposed as a promising drug delivery system for chemotherapy and molecular imaging diagnosis in MRI.